“We believe in democracy…”: Epistemic Modality in Justin Trudeau’s Political Speeches - Tofan Dwi Hardjanto; Nala Mazia (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This article investigates epistemic modality in political discourse. It focuses on modality markers in terms of their word classes, semantic meanings and discourse functions in political speeches. The data were taken from three speeches delivered by the 23rd Canadian Prime Minister Justin Trudeau. The results show that the markers found in the three speeches are of five different types, i.e., lexical verbs, modal adjectives, modal adverbs, modal auxiliary verbs and modal nouns, with meanings ranging from possibility, probability, to certainty. The markers also indicate the speaker’s commitment whose degree reflects the function in the social context. The speaker’s commitment is divided into three degrees of engagement, each of which serves as a means to be polite, to be diplomatic, and to be persuasive. The findings suggest that Trudeau tends to use reasonable judgment expressions to sound diplomatic and persuasive in his speeches.